Pengaruh Effective Tax Rate, Capital Intensity, Dan Firm Size Terhadap Profitabilitas - Erniyanti Waruwu; Fitria Eka Ningsih (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Profitability is the main goal that every company wants to achieve, both in the short and long term. In the short term, the company seeks to optimize resources to obtain maximum profits, while in the long term, profitability is the basis for increasing the company's value and shareholder welfare (Sadewa & Safitry, 2023) Good profitability performance reflects the company's ability to generate sustainable and efficient net profits. Therefore, the factors that affect profitability need to be studied in depth, especially in the industrial sector which has an important role in the national economy. This study aims to find out and test the influence of the variables Effective Tax Rate (ETR), Capital Intensity, Firm Size on profitability. This study uses non-cyclical consumer sector companies listed on the Indonesia Stock Exchange in 2021-2024. The type of research used is quantitative associative Using purposive sampling method obtained by 13 selected companies to be used as a research sample with 4 years of observation, so that the total sample in this study is 52 samples. The data analysis technique used in this study is panel data regression analysis using eviews software 12. Based on the results of the test, it shows that simultaneously the effective tax rate, capital intensity, and firm size affect profitability; partially effective tax rate, Capital intensity profitability, and capital intensity have no effect on profitability.